Genetic Algorithms - Ventura, Sebastián; María Luna, José; María Moyano, José (IntechOpen, 2022)
The solution to many real-world problems lies in optimizing processes, parameters, or techniques, which requires dealing with immense search spaces. As such, finding solutions involves exhaustive methods to evaluate all possible solutions in the search for a global optimum. Some of these methods include evolutionary algorithms and genetic algorithms, both of which have proven to effectively deal with complex search spaces. This book focuses on genetic algorithms and their applications in various fields, including engineering and architecture.